2020
DOI: 10.1021/acs.orglett.0c03308
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Meayamycin and O-Acyl Analogues

Abstract: A short, scalable total synthesis of meayamycin is described by an approach that entails a longest linear sequence of 12 steps (22 steps overall) from commercially available chiral pool materials (ethyl L-lactate, BocNH-Thr-OH, and D-ribose) and introduces the most straightforward preparation of the right-hand subunit detailed to date. The use of the approach in the divergent synthesis of a representative series of O-acyl analogues is exemplified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…This reaction obeyed the Baldwin rules 37 as only tetrahydropyranone formed (IR C�O absorption at 1716 cm −1 ). 38 This type of transformation has been previously reported only with enolboranes. 39 Ultimately (entry 5), we were delighted to see that BF 3 •OEt 2 with TBS enolsilane of ketone 43b gave aldol product 44b in 63% yield, when the reaction and quench were conducted at −80 °C.…”
mentioning
confidence: 58%
“…This reaction obeyed the Baldwin rules 37 as only tetrahydropyranone formed (IR C�O absorption at 1716 cm −1 ). 38 This type of transformation has been previously reported only with enolboranes. 39 Ultimately (entry 5), we were delighted to see that BF 3 •OEt 2 with TBS enolsilane of ketone 43b gave aldol product 44b in 63% yield, when the reaction and quench were conducted at −80 °C.…”
mentioning
confidence: 58%
“…Small molecules that bind the human spliceosome proteins have garnered interest in recent years. FR901464 and closely related small molecules represent a class of natural products that bind and modulate the function of the human splicing factor 3B (SF3B) complex. Total syntheses of FR901464 and similar natural products (Figure ) have been reported by the Jacobsen, , Kitahara, , Ghosh, Webb, Arisawa, , Nicolaou, and Boger groups and by us. We began synthesizing the A ring fragment from the l -threonine derivative, , and the Boger group improved the efficiency of the synthesis by carefully analyzing side reactions. Thus, this synthetic route appears to remain useful for the medicinal chemistry campaign.…”
mentioning
confidence: 83%
“…Boger and co-workers reported an efficient synthesis for meayamycin A ( 90 ) and its O -acyl analogues in 2020 . A short and scalable synthesis was developed utilizing the chiral pool for starting materials, in which all chirality was introduced or controlled by the chirality present in the starting materials.…”
Section: Synthesis Of Meayamycin By Boger and Co-workersmentioning
confidence: 99%
“…Known Boc-protected Garner’s aldehyde 43 was converted to amine 226 using a similar protocol reported by Koide and co-workers with only slight modifications. ,, Amine 226 was coupled with acid 16 to furnish amide 84 , whereas coupling with 42 gave amide 227 . Interestingly, it was found that utilizing acid 42 allowed for higher overall yields due to increased alcohol stability and avoidance of Z to E olefin isomerization …”
Section: Synthesis Of Meayamycin By Boger and Co-workersmentioning
confidence: 99%
See 1 more Smart Citation